Hybrid Falling Tones in Limbum - Gjersøe, Siri; Nformi, Jude; Paschen, Ludger (My University, 2019)
This paper examines the interaction between lexical tone and phrase-level into-nation in Limbum. On the basis of an acoustic study of novel data, we claim that Limbum has a phrase-final low boundary tone (L%) that interacts with lexical tones to give rise to hybrid falling tones: tones whose specifications are partially lexical and partially phrasal. We argue that hybrid tones and other tonal processes in Limbum are readily captured in an analysis that assumes tonal geometry and empty nodes. We propose to represent L% as a floating low register feature (l) that links to lexical tonal root nodes, giving rise to various surface patterns depending on the tonal specifications of the root nodes. Our account supersedes previous analyses in terms of tone sandhi rules.
Keywords: Limbum; lexical tone; Hybrid